Aspects of the biology, ecology and natural biological control of the African rice gall midge, Orseofia oryzivora Harris and Gagni (Dipt., Cecidomyiidae) in south east Nigeria - Umeh, E.D.N.; Joshi, R.C (1993)
Abstract Aspects of biology, ecology and parasitization of the African rice gall midge (ARGM), Orseolia oryzivora Harris and Gagné, were studied in the greenhouse and in the field in 1991 growing season in south east Nigeria. ARGM eggs hatched in 3 days and development (egg‐adult) was completed in 26 days. About 1/3 of the eggs laid by mated females failed to hatch. On average, 408 eggs were laid by mated females in a mean life of 3 days. Unmated females lived for 1.3 days and laid 88 eggs. Light trap catches of ARGM showed a preponderance of males early and late in the season with a female: male ratio of 1:2 and 1:3, respectively. Female: male ratio observed in the middle of the season was 1:1. Natural enemies found parasitising ARGM were Platygaster diplosisae Risbec and Aprostocetus (= Tetrastichus) pachydiplosisae Schulten and Feijen. Maximum parasitization recorded for P. diplosisae and A. pachydiplosisae was 72% and 42%, respectively. In the late season, combined parasitization by these two parasitoids reached 98 %. Certain spiders were also found to prey on adult ARGM. Zusammenfassung Zur Biologie, Ökologie und biologischen Bekämpfung der afrikanischen Reisgallmücke, Orseolia oryzivora Harris & Gagné (Dipt., Cecidomyiidae) im südöstlichen Nigeria Untersuchungen im Glashaus und im Freiland 1991 ergaben, daß die O.‐oryzivora‐Eier drei Tage nach Ablage die Larven entließen, die sich dann in 23 Tagen zu den adulten Gallmücken entwickelten. Etwa 1/3 der Eier ergaben keine Larven. Im Mittel wurden 408 Eier/♀ innerhalb von drei Tagen abgelegt. Unbefruchtete Weibchen lebten im Durchschnitt nur 1,3 Tage und legten 88 Eier ab. Lichtfallenfänge zeigten ein Übergewicht der Männchen in der Früh‐ und Spätsaison mit Weibchen/Männchen‐Quoten von 1 : 2 und 1 : 3, während in der Saisonmitte das Geschlechterverhältnis ausgeglichen war (1 : 1). Als natürliche Feinde der Reisgallmücke wurden festgestellt: Platygaster diplosisae Risbec und Aprostocetus (= Tetrastichus) pachydiplosisae Schulten & Feijen. Die maximalen Parasitierungsquoten betrugen bei P. diplosisae 72% und bei A. tachydiplosisae 42%. In der Spätsaison erreichte die Parasitierung durch beide Parasitoiden‐Arten bis zu 98%. Weiterhin wurden einige Spinnenarten als räuberische Feinde der Gallmücken festgestellt.